Pengembangan Modul Fisika Bermuatan Emotional Spiritual Quotient (ESQ) Untuk Memberdayakan Pengetahuan Dannilai Karakter Siswa SMA/MA - Darmawan, Iman; Purbaningrum, Dwi (Universitas Hamzanwadi, 2019)
This research aims at; (1) describe the characteristics of the Physics module in material with ESQ for grade X SMA / MA. (2) get Physics module with ESQ for grade X SMA / MA who are eligible based on criteria. The method of this research using R & D with the reference of model 4-D (four D model) proposed by Thiagarajan, Semmel (1974). Model 4-D consists of definition, design, development and dissemination. The module is arranged with a load of emotional spiritual quotient (ESQ) which consists of developing knowledge, students can find a solution to their problems, provide a productive learning environment, creating a learning climate of physical and social for students, and engage students optimally in learning good emotional and spiritual. In addition, the module is also equipped with guided-inquiry stage as pillars in the module because it is a part of scientific approach that needs to be developed in 2013 curriculum. The module is assessed based on the feasibility of materials, media, and languages, as well as trials (limited and extensive) to students, and the deployment phase in MGMP. Data collection of the research used questionnaires and guidelines of analysis interview, validation sheet, questionnaire responses, the character values questionnaire, observation of character value, and disseminate questionnaire. The results of the study as follows: (1) physics module which contains six components of esq were well presented, expressed or implied, with guided-inquiry basis in it. (2) modules which are categorized as an adequateone with the calculation results (matter experts, media specialists, linguists, teachers, peers) that shows the average score of 86.0> cut-off 84.3. And supported by the positive response from students and disseminate results conducted on the MGMP forum categorizing as a good module. (3) the use of the module can empower the character value and knowledge of the student because > 75% can reach more than minimum score (KKM).